2017
DOI: 10.1016/j.rfe.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Bank capital and portfolio risk among Islamic banks

Abstract: Minimum capital requirements are often implemented under the notion that increased capital improves bank safety and stability. However, an unintended consequence of higher capital requirements could arise if increasing capital induces banks to invest in riskier assets. Several researchers have examined this relationship between bank capital and risk among conventional banks, and interest around this topic has intensified since the 2007-2008 financial crisis. However, the findings are rather mixed. Moreover, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…He provides evidence that banks tend to raise their capital buffers following an increase in credit risk. Applying the Markov Chain Monte Carlo to a data set of 22 Islamic banks, Basher et al () find that an increase in total capital leads to an increase in the levels of asset risks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…He provides evidence that banks tend to raise their capital buffers following an increase in credit risk. Applying the Markov Chain Monte Carlo to a data set of 22 Islamic banks, Basher et al () find that an increase in total capital leads to an increase in the levels of asset risks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This article makes two main contributions to the existing literature. First, unlike previous studies on Islamic banks (Basher, Kessler, & Munkin, ; Daher et al, ; Ghosh, ), this article uses simultaneous equations approach to analyze the bidirectional relationship between capital buffer and credit risk. Second, we investigate the impact of the financial crisis and the presence of deposit insurance on the adjustment process.…”
Section: Introductionmentioning
confidence: 99%
“…For financing, as an example, products with the profit-sharing system is more relevant and more in accordance with sharia, but this financing system requires high monitoring costs. As a result, there is a decrease in expected future profits, so that Islamic banks tend to disburse riskier loan to increase profit (Basher, Kessler, & Munkin, 2017).…”
Section: Kata Kunci: Tingkat Kesehatan Bank; Camel; Maqasid Syariah; mentioning
confidence: 99%
“…This result was supported by Bouheni and Rachdi [6] for Tunisian banks. However, an investigation, done by Basher et al [7], of the same relationship for Islamic banks provided a disputing result. In their study of Islamic banking industry in the GCC region, they provided evidence of increased levels of asset risk as a consequence of the increased capital.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [15] investigated the effect of ownership structure on capital and risk and found a positive association. Basher et al [7] studied the effect of increased capital of Islamic banks in the GCC region on risk and stability. They found some evidence of the effect of the increased capital on the level of assets risks.…”
Section: Introductionmentioning
confidence: 99%